2018
DOI: 10.1037/gpr0000147
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment and Modeling of Perceptual Control: A Transformation in Research Methodology to Address the Replication Crisis

Abstract: Replication in the behavioral sciences is a matter of considerable debate. We describe a series of fundamental interrelated conceptual and methodological issues with current research that undermine replication and we explain how they could be addressed. Conceptually, we need a shift (1) from verbally described theories to mathematically specified theories, (2) from lineal stimulus-cognition-response theories to closed-loop theories that model behavior as feeding back to sensory input via the environment, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 104 publications
1
25
0
Order By: Relevance
“…The fact that conceptual models are expressed in verbal rather than mathematical terms has also been highlighted as a limitation. Models expressed in purely linguistic terms are inherently ambiguous and susceptible to misinterpretation (27). A consequence of this lack of specificity is that conceptual models are of limited use when trying to describe the inner organization of complex systems that are producing observable behaviour (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that conceptual models are expressed in verbal rather than mathematical terms has also been highlighted as a limitation. Models expressed in purely linguistic terms are inherently ambiguous and susceptible to misinterpretation (27). A consequence of this lack of specificity is that conceptual models are of limited use when trying to describe the inner organization of complex systems that are producing observable behaviour (33).…”
Section: Discussionmentioning
confidence: 99%
“…It might be the case that were Kazdin's recommendations for mechanistic research implemented rigorously-something that is not happening at present-it might result in the identification of plausible mechanisms (1). Recently, however, there have been calls for changes to evaluation practices to help improve the effectiveness and efficiency of psychological interventions, and to increase progress toward identifying plausible mechanisms of psychotherapeutic change (27,39,40). These changes would involve the adoption of a different approach to research practices to the one proposed by Kazdin (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a wide range of psychological treatment modalities, such as psychodynamic therapy (8) and humanistic (9) approaches. There are also many approaches derived from or compatible with computational modeling, including active inference (10) and perceptual control theory (PCT) (11,12) which make different predictions about the relationship between internal states and behavior [for example in PCT, the control of sensory input through behavior, see (11)]. It is beyond the scope of this article to cover them all, and we focus on reinforcement learning and CBT as examples, as two of the most widespread frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, tests of mechanism involve prospective studies or experimental designs (3,4). In an earlier review, we identified a number of fundamental limitations with using these methods in psychology, despite their almost universal acceptance (5). In the current article, we will begin by explaining how these limitations specifically apply to research on the mechanisms of psychological therapy.…”
Section: Introductionmentioning
confidence: 99%